THE LOGGING BAN POLICY IN ADDRESSING DEFORESTATION: A COMPARISON BETWEEN THAILAND AND INDONESIA - Safrina, Safrina (UI Scholars Hub, 2015)
The logging ban policy is applying in several countries, such as Thailand and Indonesia, in order to deal with deforestation and forest degradation in natural forests. However, both countries still have had difficulties resolving the problem. The logging ban in Thailand does not work as expected due to centralized systems of forestry policy that still applies in Thailand. However, Indonesia is actively adjusting the decentralized system, which gives authority to local governments to set policies regarding forestry. The effectiveness of logging ban to achieve conservation goals and economic development continues to be debated; however, it should be noted that the logging ban is not a standalone policy. The policy should be supported by other policy and it should also consider factors such as availability of human resources and adequate budget for the implementation. The underlying issue is also important to measure in order to formulate proper planning arrangement so that a comprehensive solution can be found to combat deforestation and forest degradation.